Reforma del art. 95 inciso segundo de la ley orgánica del sistema nacional de contratación pública, en relación a que no se admite acciones constitucionales contra las resoluciones de terminación unilateral del contrato - Quezada Verdezoto, Mirian Jeanneth (2014)
The second paragraph of Article 95 of the Organic Law of the National System of Public Procurement on the unilateral termination of the contract expresses: "If the contractor does not justify this will remedy the default or breach, in the period allowed, the Contracting Entity can unilaterally terminate the contract by order of the supreme authority of the Contracting Entity, which shall be notified in writing to the contractor and shall be published in the institutional portal of National Public Procurement SERCOP. The resolution of unilateral termination shall not be suspended by the filing of claims or administrative, administrative contentious lawsuits, arbitration or any actions or under the contractor. Neither constitutional actions against decisions of unilateral termination is allowed, because they have appropriate mechanisms and effective defenses to protect the rights under such resolutions, under the Act" This is a negative aspect of the reform is the explicit prohibition of presenting "constitutional actions" against decisions of unilateral termination. The reform justifies this ban, "because they have adequate defense mechanisms and effective protection of rights under such resolutions, under the Act"; and in the seventh paragraph of Article 102 of Law of the National System of Public Procurement extends this prohibition to all public procurement processes "procurement processes are not susceptible to constitutional actions that have adequate defense mechanisms and effective protect the rights under such process under the law "reform affecting the provisions of the right to file claims stated in the provision. However, precisely what mentions this provision to justify such a prohibition is not what happens on a day to day; currently in Ecuador still can not talk about mechanisms appropriate and effective measures to protect rights defense, considering the time it takes to obtain a court order specifically to the District Courts of Administrative, now called Units of Administrative, in normal cases, no issue their rulings before 2 or even 3 years from the filing of the complaint or appeal. What can speak effectively when dealing with the protection of possible violations of fundamental rights guaranteed in the Constitution such as due process, proper motivation and all mandatory administrative act must have, among others, whether the constitutional right is restricted individuals to present "constitutional action" against the possible effect caused by such acts of authority? Moreover, considering that many of the violations of due process, proper motivation of administrative acts and other damages to constitutional rights of individuals / bidders in public procurement processes, merit immediate and direct action of the organs of self-righteousness outside the Central Public Administration and Institutional how you can guarantee a constitutional remedy and "adequate and effective" unable to access the "constitutional actions" by legal prohibition? This also whereas other areas to go with processes related to procurement claim, are the entity that incurred the alleged violation (judge and jury) or SERCOP that only has the ability to temporarily suspend the process? Furthermore, it should also be considered something much more important: You can NOT restricted to individuals, through an amendment to the Organic Law of the National System of Public Procurement, use, enjoyment and exercise of their constitutional rights and guarantees as protective action , request for precautionary measures in such action or other. Being constitutional guarantees, they and their scope are regulated by the Constitution and the Organic Law on Jurisdictional Guarantees and Constitutional Control, to which legislation should address the constitutional judge when known. This last part is the most important: the Constitutional Court who must know such actions are filed with violations or possible violation of constitutional rights and guarantees, NOT just who is liable to the other defense mechanisms foreseen in the Law. 's the Constitution which provides resources and own to challenge violations of constitutional rights and guarantees actions, so obviously not a constitutional reform of the Organic Law of the National System of Public Procurement restrict and prohibit a particular use and enjoy these constitutional guarantees.